2018
DOI: 10.3389/fnint.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

NF-KappaB Pathway Is Involved in Bone Marrow Stromal Cell-Produced Pain Relief

Abstract: Bone marrow stromal cells (BMSCs) produce long-lasting attenuation of pain hypersensitivity. This effect involves BMSC’s ability to interact with the immune system and activation of the endogenous opioid receptors in the pain modulatory circuitry. The nuclear factor kappa B (NF-κB) protein complex is a key transcription factor that regulates gene expression involved in immunity. We tested the hypothesis that the NF-κB signaling plays a role in BMSC-induced pain relief. We focused on the rostral ventromedial me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 55 publications
1
16
0
Order By: Relevance
“…For example, in sciatic nerve CCI model mice [ 22 , 33 ], intrathecal BMSCs exerted a persistent analgesic effect through the release of the anti-inflammatory growth factor transforming growth factor beta, which inhibited CCI-induced spinal neuroinflammation, downregulated TNF- α expression, and modulated excitatory synaptic transmission in spinal cord and dorsal root ganglion neurons [ 22 , 33 ]. Nuclear factor kappa B (NF- κ B) signaling plays a key role in BMSC-induced antihyperalgesia in rat models of persistent pain and spinal cord injury [ 34 , 35 ]. In spinal cord injury rats, BMSCs downregulated phosphorylated NF- κ B P65 subunit and decreased other proinflammatory factors, such as TNF- α and IL-1 β [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in sciatic nerve CCI model mice [ 22 , 33 ], intrathecal BMSCs exerted a persistent analgesic effect through the release of the anti-inflammatory growth factor transforming growth factor beta, which inhibited CCI-induced spinal neuroinflammation, downregulated TNF- α expression, and modulated excitatory synaptic transmission in spinal cord and dorsal root ganglion neurons [ 22 , 33 ]. Nuclear factor kappa B (NF- κ B) signaling plays a key role in BMSC-induced antihyperalgesia in rat models of persistent pain and spinal cord injury [ 34 , 35 ]. In spinal cord injury rats, BMSCs downregulated phosphorylated NF- κ B P65 subunit and decreased other proinflammatory factors, such as TNF- α and IL-1 β [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cells were fixed with 4% paraformaldehyde for 10 min at room temperature as described [ 37 ]. Immunostaining of p65 was done as described above [ 38 ]. Secondary, AlexaFluor 647-conjugated donkey anti-goat antibody was used at a concentration of 1:1000 (Thermofisher, USA) for 90 min.…”
Section: Methodsmentioning
confidence: 99%
“…We finally verified whether the bite force measure could be used to detect pain-relief. We have shown that transplantation of BMSCs produces long-lasting pain relief in TL rats [17][18][19][20]. Since BMSCs are able to avoid immune rejection likely due to a lack of major histocompatibility complex class II molecules and co-stimulatory surface markers for T-cell activation [30], we infused rat BMSCs to mice.…”
Section: Effect Of Bone Marrow Stromal Cells On Bite Forcementioning
confidence: 99%
“…Transplantation of human or rat BMSCs produces long-term attenuation of hyperalgesia/allodynia (antihyperalgesia) in rodents [17,59]. Assessed with the von Frey method and CPA behavioral test, we have shown previously that TL-induced pain hypersensitivity was attenuated by BMSCs [17][18][19][20]. Although the majority of systemic BMSCCs are trapped in the lungs after infusion and stayed in the body for no more than a few weeks, they produce antihyperalgesia that lasts for a few months, involving immune interactions and activation of the endogenous opioids [19,60].…”
Section: The Effect Of Pain-relieving Bmscsmentioning
confidence: 99%
See 1 more Smart Citation